SERANGGA PEROMBAK BAHAN ORGANIK DI PEKARANGAN TELUKNAGA, CITEUREUP DAN PACET - AMIR, M.; ATMOWIDJOJO, ANITA H. (BERITA BIOLOGI, 1985)
M. AMIR & ANITA H. ATMOWIDJOJO.1985. Insect decomposers of organic materials in the kitchen gardens in Teluknaga, Citeureup and Pacet.Berita Biologi 3 (2) : 66 - 69. Studies on insect decomposers of home gardens at Teluknaga, Citeureup and Pacet were carried out to obtain information on their distribution and species diversity on plant and animal litters.The result indicated that the species composition of the insect decomposer at the three places (kecamatan) were not significantly different. It seemed that the insects were not affected by the different ground cover vegetation. Among the insect decomposers, termites were the most important. These insects were found to occupy different types of litters. The other insect decomposers, e.g. Gryllotafpa sp., Copris sp. and a species of Nitidulidae, were found in plant and animal litteis.